P44 Train the trainer: using simulation to enhance the development of cell salvage education programmes. (31st December 2017) - Fores, M; Chambers, M; Natarajan, R; Bailey, P
Abstract : Introduction: This course was developed collaboratively with Fresenius Kabi Ltd as part of a training programme for experienced cell salvage trainers. The aim was to help develop trainers with the knowledge and skills to teach, mentor and assess use of cell salvage within their hospitals and so provide a safe and efficient service in clinical practice. Training and competency for cell salvage operators should be in place in all organisations where cell salvage is undertaken (SHOT, 2011). There is also a need for co-ordination of the expert skills and knowledge to help drive the wider implementation of Intraoperative cell salvage in the UK (UK Cell Salvage Action Group 2016). Methods: The full day course was co-designed with industry partners and combines workshops with full immersion simulation exercises using the Fresenius CATS Continuous Auto Transfusion System. It has run on 5 occasions with 57 attendees, including Operating Department Practitioners, Nurses, Anaesthetists and Perfusionists. Pre and post course questionnaires were used for evaluation. Results: The pre-course evaluations showed that only 26% of the delegates considered themselves expert cell salvage operators and 29% felt confident in cell salvage operation. The post-course evaluations were very positive and 93% stated they had gained new skills that they could use within their own cell salvage practice and training. Free text feedback highlighted the value of hands on practice and shared experience. Discussion: A point for discussion was that this course may not have been suitable for all candidates due to their level of exposure and experience in cell salvage. A review of delegate selection criteria with reference to their cell salvage experience was proposed to facilitate maximum benefit from the training provided by this course. This was not evidenced in the delegates' feedback as the scores for improved knowledge and skills that could be taken forward into their own practice were very high. Recommendation: The course was very positively evaluated and candidates on subsequent courses will be followed up with a post course questionnaire exploring translation of learning into clinical practice. It is a recommendation to continue with the course in its current format for cell salvage trainers. The framework could be adapted and reproduced to develop faculty as trainers for other clinical devices. This demonstrated a synergy with industry partners that could be replicated to benefit patient care in a wider context. Acknowledgements Fresenius Kabi Ltd. References: . SHOT. Serious Hazards of Transfusion (SHOT). Affiliated to the Royal College of Pathologists 2011 (Annual Report 2011). . UK Cell Salvage Action Group. JPAC Joint United Kingdom (UK ) Blood Transfusion and Tissue Transplantation Services Professional Advisory Committee 2016. Date accessed 24/05/2016. http://www.transfusionguidelines.org/transfusion-practice/uk-cell-salvage-action-group/introduction